Multimodal Elements of Suicidality Reduction After Transcranial Magnetic Stimulation. Issue 5 (1st March 2021) - Barredo, Jennifer; Berlow, Yosef; Swearingen, Hannah R.; Greenberg, Benjamin D.; Carpenter, Linda L.; Philip, Noah S.
Abstract: Objectives: Repetitive transcranial magnetic stimulation (TMS) is a promising treatment for suicidality, but it is underlying neural mechanisms remain poorly understood. Our prior findings indicated that frontostriatal functional connectivity correlates with the severity of suicidal thoughts and behaviors. In this secondary analysis of data from an open label trial, we evaluated whether changes in frontostriatal functional connectivity would accompany suicidality reductions following TMS. We also explored the relationship between frontostriatal connectivity change and underlying white matter (WM) organization. Materials and Methods: We conducted seed‐based functional connectivity analysis on participants ( N = 25) with comorbid post‐traumatic stress disorder and depression who received eight weeks of 5 Hz TMS to left dorsolateral prefrontal cortex. We measured clinical symptoms with the Inventory of Depressive Symptomatology‐Self Report (IDS‐SR) and the PTSD Checklist for DSM‐5 (PCL‐5). We derived suicidality from IDS‐SR item 18. Magnetic resonance imaging data were collected before TMS, and at treatment end point. These data were entered into analyses of covariance, evaluating the effect of suicidality change across treatment on striatal and thalamic functional connectivity. Changes in other PTSD and depression symptoms were included as covariates and results were corrected for multiple comparisons. Diffusion connectometry in a participant subsample ( N = 17) explored the relationship between frontal WM integrity at treatment baseline and subsequent functional connectivity changes correlated with differences in suicidality. Results: Suicidal ideation decreased in 65% of participants. Reductions in suicidality and functional connectivity between the dorsal striatum and frontopolar cortex were correlated ( p ‐False Discover Rate‐corrected < 0.001), after covariance for clinical symptom change. All other results were nonsignificant. Our connectometry results indicated that the integrity of frontostriatal WM may circumscribe functional connectivity response to TMS for suicide. Conclusions: Targeted reduction of fronto‐striatal connectivity with TMS may be a promising treatment for suicidality. Future research can build on this multimodal approach to advance individualized stimulation approaches in high‐risk patients.